(untitled) (Comunicação & Inovação, 2024)
The study aimed to identify whether Brazilian television companies have the organizational capabilities to implement Frugal Innovation in the development of digital technologies. The research methodology was mixed: qualitative, through content analysis of transcripts extracted from the interviews; and quantitative, through the use of a validated instrument to measure Frugal Innovation. Technology results from the pilot identified a significant cost reduction after replacing content transport, or the high-cost bus or van equipment for each vehicle, with backpack transport equipment. capable of transmitting audio and video over the Internet, using a 4G mobile data network.